Can the location of the isolation laboratory affect the generation of myxomycete data using moist chambers? An experiment in the Neotropics - Rojas Alvarado, Carlos Alonso (2021)
The moist chamber technique, as it is used in myxomycete research, is an extremely useful method to optimize project resources. However, as it occurs with any laboratory-based protocol, the usefulness of this technique should be evaluated using contextual elements, most of which, are lacking in the literature. The present study evaluated the results obtained using the moist chamber technique with the same substrate material, synchronously, in two different laboratories in Costa Rica. Using climate data obtained at both isolation localities and microclimate data obtained directly from the moist chambers, an analysis of differences in results was attempted. Even though variations in results are intrinsic to biological surveys, the results presented herein suggested that some recorded differences could have been linked to the air humidity and the temperature of the moist chamber culture. Even though the two laboratories were only 30 km apart, an average difference of 8.5% in the values of the diversity indices was observed. Also, between 15% and 19% of the species recorded in the total dataset were only observed in one laboratory. In this manner, the present study is useful to keep in mind that myxomycete results using the moist chamber technique, can be extremely influenced by variables that are usually not considered in the general application of the protocol. Perhaps it is time to work on an optimized version of such useful technique.